Effects of dystocia and confined calving on calf-morbidity rate from birth to weaning - M.W. Sanderson; D.A. Dargatz (Kansas Agricultural Experiment Station Research Reports, 2000)
An analysis was performed on data from a national survey of US beef cow-calf producers to quantify the effects of management factors on calf-morbidity risk from birth to weaning. The analysis included 2,490 herds from 23 states. A high calf-morbidity herd was defined as one with greater than 10% morbidity. The rate of dystocia in the herd was categorized into five levels. All dystocia levels were associated significantly with increased risk of being a high calf-morbidity herd. Having greater than 70% of cows and heifers calve in confinement also was associated with increased risk of being a high calf-morbidity herd. Approximately 40% of herds experienced high morbidity from the effect of dystocia and approximately 10% from the effect of confined calving. This analysis indicates that dystocia and confined calving are important factors in determining a herd's calfmorbidity rate from birth to weaning.
Keywords: Cattlemen& #x27; s Day; 2000; Kansas Agricultural Experiment Station contribution; no. 00-287-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 850; Beef; Cow-calf; Calf morbidity; Calving; Dystocia